Ecotoxicological Assessment of “Glitter” Leachates in Aquatic Ecosystems: An Integrated Approach - Manuela Piccardo; Francesca Provenza; Serena Anselmi; Monia Renzi (Toxics, 2022)
The most worrisome fraction within plastic pollution is that of microplastics (MP). A category of MP almost completely ignored is that of glitter. The objective of this study is to test the toxicity of nine types of glitter leachate (3 soak times: 3, 90 and 180 days) on model organisms in freshwater (Allivibrio fischeri, Raphidocelis subcapitata, Daphnia magna) and saltwater (Allivibrio fischeri, Phaeodactylum tricornutum, Paracentrotus lividus). An integrated approach was applied to obtain the percentage of ecotoxicological risk. The results show that (i) photosynthesizing primary producers are the most sensitive trophic level; (ii) algae transitioned from growth inhibition to biostimulation; (iii) D. magna showed higher sensitivity after 48 h compared to 24 h; (iv) A. fischeri responded more strongly in saltwater than in freshwater. The integrated data show a greater risk associated with the marine environment, with the highest risk for glitters that are hexagonal and composed of poly-methyl-methacrylate. Our multivariate analysis shows that the toxicity of plastic leaching is a complex phenomenon that depends on the sensitivity of the species, in some cases on the soaking time and on the medium, and is not clearly linked to the polymer type, the contact area or the colors of the particles.